Sistem Pendukung Keputusan Berbasis Web dengan Metode AHP-TOPSIS untuk Pengukuran Tingkat Kesejahteraan Masyarakat Pesisir di Kabupaten Pidie - Husnaini, Nurul Fauziah (Computer Journal, 2025)
The welfare of coastal communities in Pidie Regency still faces major challenges, especially related to poverty, where the majority of the population works as fishermen. This study aims to design a web-based decision support system (DSS) using the Analytical Hierarchy Process (AHP) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to measure the level of welfare of coastal communities. The AHP method is used to determine the weight of the criteria, while TOPSIS is used to assess and rank the level of welfare. This system was developed using the PHP programming language and implemented through the XAMPP application. The results of the study show that this system is able to provide accurate and efficient information related to the level of welfare, so that it can be a reference for the government in formulating coastal community development policies.